ANALISIS FAKTOR RISIKO KEJADIAN ISPA DITINJAU DARI STATUS RUMAH DI WILAYAH KERJA PUSKESMAS KOTA WILAYAH UTARA KOTA KEDIRI - Ema Mayasari (Universitas Jember, 2015)
Acute Respiratory Infections (ARI) is one of the most common causes of death in children of developing countries. The cause of ARI include home building materials made of asbestos, has a floor with a thickness of less than 20cm and has a floor area of less than 10% of the floor area. The objective of this study was to determine the effect of physical condition to Acute Respiratory Infections (ARI) at public health centers in the region of the northern town of Kediri. This study was an analytic study with cross-sectional approach. There were 102 samples on society at public health centers in the region of the northern town of Kediri, and use simple random sampling. The independent variable is the building constructures, the type of floor, and size of ventilation, while the dependent variable was the incident of Acute Respiratory Infection. Data were analyzed by logistic regression.The results showed that, p value = 0,000 <α =0,05, so there is physical condition home has affected the occurrence ARI. While the most dominant factor of the three factors is size of ventilation where the value of Exp (B) 0,014 more than the other two factors, are building contructure where the value Exp (B) 0,012 and the type of floor where the value Exp (B) 0,010.The majority of respondents suffering from ARI and most the of respondent have a home ventilation that does not qualify, therefore people should pay more attention to the ventilation of their homes so spacious home ventilation of at least 10 % of their floor area. Keywords: Acute Respiratory Infection, Building Material, Floor, Ventilation